Ascending Aortic Strain Analysis Using 2‐Dimensional Speckle Tracking Echocardiography Improves the Diagnostics for Coronary Artery Stenosis in Patients With Suspected Stable Angina Pectoris. Issue 14 (17th July 2018) - Bu, Zhaohui; Ma, Jun; Fan, Yibo; Qiao, Zhiqing; Kang, Yu; Zheng, Ying; Wang, Wei; Du, Yongping; Zheng, Zheng; Shen, Xuedong; He, Ben; Pu, Jun
Abstract : Background: Arterial stiffening and atherosclerosis tend to coexist. Strain imaging, using a 2‐dimensional speckle tracking (2D‐ST) method, has been used for arterial stiffness assessment and early identification of atherosclerosis. We investigated whether the ascending aortic strain assessed by 2D‐ST echocardiography at rest can predict the presence of coronary artery disease (CAD). Methods and Results: Two hundred seventy‐one consecutive patients with suspected stable angina pectoris sequentially underwent exercise treadmill testing, 2‐dimensional echocardiography, M‐mode echocardiography, 2D‐ST echocardiography, and coronary angiography. Circumferential ascending aortic strain (CAAS) and radial ascending aortic strain were assessed by 2D‐ST echocardiography. Ninety‐two patients with coronary lumen area stenosis ≥70% were categorized as having significant CAD. Global CAAS was significantly lower in patients with significant CAD (7.41±2.30% versus 11.54±4.03%; P <0.001) and remained an independent predictor of significant CAD (odds ratio, 0.64 [0.54–0.75]; P <0.001) after multivariate regression. Based on the receiver operating characteristic curve for diagnosing significant CAD, the optimal cut‐off value of global CAAS was ≤9.22% (sensitivity, 86%; specificity, 70%; area under curve=0.82; P <0.001). Global CAAS decreased with increasing severity of CAD and was significantly associated with 3‐vessel disease (odds ratio, 0.58 [0.42–0.79]; P <0.001). Diagnostics for significant CAD were remarkably better for global CAAS combined with exercise treadmill testing than for exercise treadmill testing alone (area under curve=0.88 versus 0.78; P <0.001). Conclusions: Global CAAS assessed by 2D‐ST echocardiography at rest was able to predict the presence of significant CAD and identify multivessel disease. In addition, global CAAS combined with exercise treadmill testing remarkably improved the diagnostics for significant CAD.